2015
DOI: 10.1002/eat.22435
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and eating behavior in adolescent girls at risk for type 2 diabetes

Abstract: Objective The purpose of this investigation was to examine the relationship of dispositional mindfulness to binge eating and associated eating attitudes and behaviors among adolescent girls at risk for type 2 diabetes (T2D). Methods Participants were 114 overweight or obese adolescents enrolled in a study of girls with a family history of T2D and mild depressive symptoms. Adolescent self-reports of mindfulness, eating in the absence of hunger, and depressive symptoms were collected. An interview was administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 42 publications
2
35
1
3
Order By: Relevance
“…In other studies of non-clinical samples of adults using self-report surveys, dispositional mindfulness also has been inversely associated with reported eating in response to emotions (Pidgeon, Lacota, & Champion, 2013), disordered eating symptoms (Masuda, Price, & Latzman, 2012), and fewer symptoms of disinhibited-type eating disorders such as bulimia nervosa (Lavender, Jardin, & Anderson, 2009). In a prior cross-sectional study of overweight and obese adolescent girls, dispositional mindfulness was related to a lower odds of reported binge-eating, less frequent reported-EAH in response to fatigue or boredom, and less reinforcing value of food (Pivarunas et al, 2015). Although existing data have primarily relied upon self-reports of disinhibited eating, one previous study of college students found that an experimental mindfulness induction led to greater enjoyment of eating paired with less energy intake from unhealthy “junk” foods in the laboratory (Arch et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies of non-clinical samples of adults using self-report surveys, dispositional mindfulness also has been inversely associated with reported eating in response to emotions (Pidgeon, Lacota, & Champion, 2013), disordered eating symptoms (Masuda, Price, & Latzman, 2012), and fewer symptoms of disinhibited-type eating disorders such as bulimia nervosa (Lavender, Jardin, & Anderson, 2009). In a prior cross-sectional study of overweight and obese adolescent girls, dispositional mindfulness was related to a lower odds of reported binge-eating, less frequent reported-EAH in response to fatigue or boredom, and less reinforcing value of food (Pivarunas et al, 2015). Although existing data have primarily relied upon self-reports of disinhibited eating, one previous study of college students found that an experimental mindfulness induction led to greater enjoyment of eating paired with less energy intake from unhealthy “junk” foods in the laboratory (Arch et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We anticipated that there would be an inverse relationship between mindfulness and EAH based on the notion that mindfulness encourages noticing, accepting, and differentiating among internal and external experiences (Hill et al, 2015), which may translate to an increased ability to self-regulate eating. Because mindfulness is related to reported LOC-eating patterns (Pivarunas et al, 2015), we sought to determine the relationship of mindfulness to EAH after accounting for LOC-eating, in order to ensure that any identified findings indicated a unique association of mindfulness with EAH. As a secondary objective, we explored the interaction of mindfulness and LOC in the prediction of laboratory eating behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that dispositional mindfulness was associated with lower odds of binge eating, as assessed by the EDE-Q (Eating Disorder Examination-Questionnare). Additionally, mindfulness was found to be inversely associated with eating concerns, EAH in response to fatigue or boredom, and higher food reinforcement compared to physical activity [47].…”
Section: Studies On Targeted Prevention (High Risk Cohorts)mentioning
confidence: 93%
“…Pivarunas et al [47] conducted a similar study among overweight and obese (BMI >85th age percentile) adolescent girls aged 12-17 years (n = 114) at risk of type 2 diabetes in order to examine the relationship between dispositional mindfulness and binge eating, as well as dietary restraint, and eating, shape, and weight conerns. The Relative Reinforcing Value of Food Task was administered to determine the reinforcing value of each participant's preferred snack food in relation to one of three alternate rewards.…”
Section: Studies On Targeted Prevention (High Risk Cohorts)mentioning
confidence: 99%
“…4748 Even before this landmark study, Medicare began providing reimbursement for diabetes self-management training provided by a qualified clinician—including non-physician providers such as diabetes educators. 49 Obesity research has identified psychological and executive function factors such as mindfulness 50 and negative affect 51 as potential positive and negative contributors to loss of control eating in children—a precursor to adult binge-eating disorders. Leading health organizations—including the World Health Organization, 25 the U.S. Department of Health and Human Services, 52 and the Institute of Medicine (IOM) 53 —recognize the important role social determinants play in disease prevention and management.…”
Section: Opportunities For Expanding Luts Researchmentioning
confidence: 99%